Association between long-term exposure to ambient particulate matter and pulmonary function among men and women in typical areas of South and North China - Liu, Qihang; Pan, Li; Yang, Ting; Ou, Qiong; Sun, Zhiwei; He, Huijing; Hu, Yaoda; Tu, Ji; Lin, Binbin; Lao, Miaochan; Liu, Chang; Li, Baicun; et al. (Frontiers in Public Health, 2023)
Background Studies comparing the effects of different sizes and concentrations of ambient particulate matter (PM) on pulmonary function in different regions and sexes remain sparse. Objectives To investigate the associations of different sizes and levels of long-term ambient PM exposure with pulmonary function among people of different sexes in typical areas of South and North China. Methods In 2021, a total of 1,592 participants aged 20–73 years were recruited to participate in the pulmonary function test from the baseline survey of the Diverse Life-Course Cohort (DLCC) in typical areas of Guangdong Province and Hebei Province. The three-year (2018–2020) average ambient PM concentrations were assessed from the ChinaHighPM1 dataset, ChinaHighPM2.5 dataset and ChinaHighPM10 dataset. Mean differences in pulmonary function were used in multilevel models for different regions and sexes. Results We discovered significant associations of ambient PM exposure with reduced forced vital capacity (FVC) and increased forced expiratory volume in 1 s/forced vital capacity ratio (FEV1/FVC) among men and lower levels of FEV1 and FVC among women, such that a 5-μg/m3 concentration increase in PM1, PM2.5, and PM10 was associated with decreases in FVC of 122.1 ml (95% confidence interval (CI): 30.8, 213.4), 54.6 ml (95% CI: 15.8, 93.3) and 42.9 ml (95% CI: 12.7, 73.1) and increases in FEV1/FVC of 2.2% (95% CI: 0.6, 3.9), 1.1% (95% CI: 0.4, 1.9) and 0.9% (95% CI: 0.3, 1.5) among men and decreases in FEV1 of 51.1 ml (95% CI: 9.7, 92.4), 21.6 ml (95% CI: 4.3, 38.9) and 16.7 ml (95% CI: 3.3, 30.1) and in FVC of 77.8 ml (95% CI: 10.0, 145.6), 38.7 ml (95% CI: 9.0, 68.5) and 31.1 ml (95% CI: 8.1, 54.1) among women in Hebei Province. There was no association between ambient PM and pulmonary function in Guangdong Province. Conclusion Long-term exposure to different sizes and concentrations of ambient PM were associated with FEV1 and FVC among men and women differently. The impact of ambient PM on FVC should be of greater concerned.